Estimating One’s Own and One’s Relatives’ Multiple Intelligence: A Study from Argentina - Furnham, Adrian; Chamorro-premuzic, Tomas (The Spanish Journal of Psychology, 2005)
Participants from Argentina (N = 217) estimated their own, their partner’s, their parents’ and their grandparents’ overall and multiple intelligences. The Argentinean data showed that men gave higher overall estimates than women (M = 110.4 vs. 105.1) as well as higher estimates on mathematical and spatial intelligence. Participants thought themselves slightly less bright than their fathers (2 IQ points) but brighter than their mothers (6 points), their grandfathers (8 points), but especially their grandmothers (11 points). Regressions showed that participants thought verbal and mathematical IQ to be the best predictors of overall IQ. Results were broadly in agreement with other studies in the area. A comparison was also made with British data using the same questionnaire. British participants tended to give significantly higher self-estimates than for relatives, though the pattern was generally similar. Results are discussed in terms of the studies in the field.